Outbreak of Respiratory Tract Infection Score (ORTIS): Objective Screening for Children to Rule Out COVID-19 and Prevent Nosocomial Spread - Varnit Shanker (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Since December 2019, over two million people worldwide have been affected by coronavirus disease 2019 (COVID-19). Because of quarantine measures, overcrowded healthcare facilities, fear of contracting the disease and forced behavioural modification to suspect every respiratory tract infection as a potential COVID-19 case - parents of sick children are hesitant to contact healthcare facilities in developing countries such as India. Acute shortage of specialist care has led to increased suffering of children affected by other diseases.